Pipe de lut cu inscripții și mărci din colecția I.C.E.M. Tulcea - Iuliana COSTEA (Peuce, 2013)
The archaeological excavations in Tulcea County have lead to the identification of an important number of clay pipes and fragments of pipes, proof that tobacco was smoked in Dobrudja Province, as well as in the Balkan Peninsula and Ottoman Empire since the beginnings of the 17th century. In this article, we analyze the makers’ stamps and the inscriptions in Arabic that have been preserved on these artefacts. The stamps represent names of craftsmen, such as Yekta, Hüsnü or Babalık, some of them renowned for the quality of the clay pipes manufactured in their workshops from Tophane, a district of Istanbul, where the pipe-makers guild was established in the second half of the 18th century.